Diversitas dan Distribusi Alga Merah (Rhodophyta) di Perairan Pulau Ternate - Ardan Samman; M. Janib Achmad (Jurnal Kelautan Tropis, 2023)
Red algae (Rhodophyta) are low-level plants that generally grow attached to certain substrates such as coral, mud, sand, rocks and other massive objects. This type of algae take nutrients from the substrate by diffusion through the walls from its thallus. This alga prefers habitat of clear waters that have substrate base of coral, dead coral, volcanic rocks or massive objects. Red algae can be found in intertidal, subtidal to coastal areas with strong waves and currents as well as in mangrove area. This study aims to determine the diversity and distribution patterns and associations of red algae in seagrass ecosystems and coastal coral reefs of Ternate Island. The method used in this study is a descriptive method with sampling by line-transect quadrat (1x1 meter). The sampling locations were divided into three stations. Data were analyzed descriptively and the number of red algae (Rhodophyta) found at each station was included in a distribution map based on depth and density index. The results showed that the total number of individuals found at the three stations was 33, where ST II dominated with 12 with an average of 3 individuals per depth. Distribution of individuals per depth at ST II was highest at a depth of 10 m with 4 individuals, followed by a depth of 5 and 15 m each with 3 individuals, a depth of 25 m was 1 individual, and no individual was found at 20 m depth. Substrate type at a depth of 10 m was dominated by coral and sandy fractures that could support well the growth and development of red algae.